Therapeutic effect and safety of Wei-Fu-Chun in the treatment of chronic atrophic gastritis: a network meta-analysis - Wu, Yunbo; Hu, Ling (Frontiers in Pharmacology, 2025)
IntroductionChronic atrophic gastritis (CAG) is a chronic condition characterized by a reduction in gastric mucosal glands and is often regarded as a precursor to gastric cancer. Currently, Western medicine lacks specific treatments for CAG, with management primarily focusing on symptomatic relief and, in cases involving Helicobacter pylori infection, eradication therapy. This study employs a network meta-analysis (NMA) to evaluate the efficacy and safety of the Chinese patent medicine Wei-Fu-Chun (WFC) in the treatment of CAG.MethodsWe systematically reviewed randomized controlled trials (RCTs) comparing WFC with other interventions for CAG. The outcomes assessed included clinical effectiveness, gastrointestinal symptom scores, gastrointestinal hormone levels, and adverse reactions. The quality of the included studies was assessed with the Cochrane Handbook and GRADEpro software based on the following criteria: random sequence generation, allocation concealment, blinding of participants and personnel, blinding of outcome assessment, completeness of outcome data, and selective reporting. Risk ratios were calculated for dichotomous outcomes, and standardized mean differences with 95% confidence intervals were used for continuous variables. Funnel plots were generated to assess publication bias, and treatments were ranked using the surface under the cumulative ranking curve (SUCRA). Data analysis was performed using STATA 15.0 and Review Manager 5.3. The protocol has been registered with PROSPERO under the registration number CRD420251056533.ResultsA total of 38 RCTs involving 3,844 participants were included, and 10 interventions were evaluated: conventional therapy, prokinetics, mucosal-protective agents (MPAs), acid-suppressing drugs (ASDs), H. pylori eradication therapy (HET), WFC, WFC + prokinetics, WFC + MPAs, WFC + ASDs, and WFC + HET. The majority of the included studies were evaluated as having a low risk of bias regarding randomization, attrition, reporting, and other domains, while the risk of bias remained unclear for allocation concealment and blinding. Sensitivity analysis revealed that excluding any single study had a minimal influence on the overall pooled results, and statistical heterogeneity was negligible. The NMA results indicated that WFC combined with MPA ranked the highest in overall clinical efficacy, while WFC combined with prokinetics was the most effective in restoring gastrin (GAS)/motilin (MTL) levels and alleviating symptom burden. WFC monotherapy also outperformed several Western medications (e.g., MPA, acid inhibitors, and conventional therapy) across multiple outcomes. Combinations of WFC with acid suppressants or prokinetics were associated with fewer adverse events than monotherapies, suggesting a potential reduction in drug-related side effects.ConclusionWFC, particularly in combination with Western medications, enhances clinical efficacy and reduces the incidence of adverse events in patients with CAG. These findings support its potential as a therapeutic option for improving clinical outcomes in CAG.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251056533.